The Mediation Role Of Attitude Applied To The TRA Model And TPB Model In Environmentally Friendly Products Of Food Industry Sector In Indonesia Smes - Anggalia Wibasuri; Kurnia Fadila (Green Publisher Indonesia, 2024)
Purpose: to the explore the Theory Reaction Action model and Theory Planned Behavior model in Environmentally Friendly Products of Food Industry Sector in Indonesia SMEs. Design/methodology/approach: This research uses a qualitative-exploratory and quantitative research, with analysis of factors affecting the purchase of environmentally friendly products by emphasizing the enrichment aspect in the field as the strength of research. As a study that not only comes to describe the problem only but this research will come to the stage of drafting the development model, and applicative by conducting observations and evaluation in the field. Findings: 1) the hypothesis that customer knowledge has a positive and significant effect on purchase intentioncan be accepted. 2) the hypothesis that customer knowledge has apositive and significant effect on Environment Friendly Products can be accepted. 3) the hypothesis that the influence of consumer attitudes on the environment has a positive and significant effect on purchase intention of environmentally friendly products can be accepted. Originality: The Mediation Role of Attitude Applied to the TRA Model and TPB Model in Environmentally Friendly Products.